Lithiation and Delithiation Properties of Silicide/Si Composite Alloy Electrodes Prepared by Rapid Quenching Method - Yuta KIMURA; Yasuhiro DOMI; Hiroyuki USUI; Hiroki SAKAGUCHI (Electrochemistry, 2020)
Rapid quenching is one of the methods for preparing silicide/Si composite alloy as an active material for negative electrode in lithium-ion batteries. In this study, we focused on the method’s control over the positional relation between the Si and silicide phase by changing the additive elements. Various Si-alloys and the relationship between their lithiation and delithiation properties and their arrangement was investigated.